Sun protection and occupation: Current developments and perspectives for prevention of occupational skin cancer - Cara Symanzik; Cara Symanzik; Swen Malte John; Swen Malte John (Frontiers Media S.A., 2022)
A substantial proportion of all reported occupational illnesses are constituted by skin cancer, making this disease a serious public health issue. Solar ultra-violet radiation (UVR) exposure is the most significant external factor in the development of skin cancer, for which the broad occupational category of outdoor workers has already been identified as high-risk group. Sun protection by deploying adequate technical, organizational, and person-related measures has to be understood as a functional aspect of workplace safety. To prevent skin cancers brought on by-typically cumulative-solar UVR exposure, outdoor workers must considerably lower their occupationally acquired solar UVR doses. Estimating cumulative sun exposure in outdoor workers requires consideration of the level of solar UVR exposure, the tasks to be done in the sun, and the employees' solar UVR preventive measures. Recent studies have highlighted the necessity for measures to enhance outdoor workers' sun protection behavior. In the coming decades, occupational dermatology is expected to pay increasing attention to sun protection at work. Also, the field of dermato-oncology will likely be concerned with sky-rocketing incidences of occupational skin cancers. The complete range of available alternatives should be utilized in terms of preventive actions, which seems pivotal to handle the present and future challenges in a purposeful manner. This will almost definitely only be possible if politicians' support is effectively combined with communal and individual preventive actions in order to spur long-term transformation.